(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article analyzes international film co-productions as a form of cultural diplomacy and a mechanism of soft power. Based on a comparative analysis of practices in Ukraine and the United States, the legal framework, institutional mechanisms, and economic and communicative effects of co-productions are examined. The paper offers practical recommendations for states and filmmakers.